How do you solve –2(x – 3) ≥ 5 – (x + 3)?

1 Answer
May 18, 2018

4 ≥ x

x is less than 4.

Explanation:

-2(x - 3) ≥ 5 - (x + 3)

First, distribute. x and -3 will be multiplied by -2 because they're in parentheses, per PEMDAS. The - will be distributed to x and 3 because they're also in parentheses.

-2x + 6 ≥ 5 -x -3

Combine like terms.

-2x + 6 ≥ 2 - x

Now, negate the smallest variable. In this case, it's -2x, so add 2x to both sides to cancel it out.

6 ≥ 2 + x

Now, subtract 2 from both sides to isolate for x:

4 ≥ x

x is less than 4.